(3GdeONd Gdi Jehjd GdJLGQI GdNGQLjI s - (3aWjeI(B, (3MGLjs ((3GdLRGFQ(B:s (3OjhGf GdeWHhYGJ GdLGeYjI(B,s, 2017)
(3jOQS gPG GdcJGH Jehjd GdJLGQI GdNGQLjI, hJMOjOG JbfjGJ hCOhGJ GdOaY GdeSJNOeI aj GdJLGQI GdOhdjI, ceG jgOa GdcJGH cPdc Edi GHQGR ehGVjY eJYdbI HGdJLGQI GdOhdjI cGdVeGfGJ GdOhdjI, hJCejf GdJLGQI GdOhdjI, HGdEVGaI Gdi GdJaGhV GdJLGQj GdOhdj, NGUI aj Xd GdJMhdGJ GdLOjOI hGdJWhQGJ GdMGdjI hGdeSJbHdjI ddJLGQI GdOhdjI , hjLjH GdcJGH CjVG Yf HYV GdCSFdI ef TcjdI(B: (3eG GdebUhO HGdJehjd GdOhdj? eG CgejI GdJLGQI GdOhdjI? s
(3eQGLY U(B.193 (3edGMb U(B.205s
Keywords: (3GdJLGQI GdNGQLjI (B- (3Jehjds